1997
DOI: 10.1016/s0304-3959(97)00138-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain processing during three levels of noxious stimulation produces differential patterns of central activity

Abstract: Previous functional imaging studies have demonstrated a number of discrete brain structures that increase activity with noxious stimulation. Of the commonly identified central structures, only the anterior cingulate cortex shows a consistent response during the experience of pain. The insula and thalamus demonstrate reasonable consistency while all other regions, including the lentiform nucleus, somatosensory cortex and prefrontal cortex, are active in no more than half the current studies. The reason for such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
300
2
12

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(347 citation statements)
references
References 29 publications
33
300
2
12
Order By: Relevance
“…The rostal part of the ACC, which is connected to the amygdala and the periaqueductal gray matter (PAG), modulates the internal emotional response to pain [9]. The frontal gyri are consistent with activations identified in previous human experimental neuroimaging studies of pain [10]. The different functional networks indicated that the baseline changed after the needle manipulation.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The rostal part of the ACC, which is connected to the amygdala and the periaqueductal gray matter (PAG), modulates the internal emotional response to pain [9]. The frontal gyri are consistent with activations identified in previous human experimental neuroimaging studies of pain [10]. The different functional networks indicated that the baseline changed after the needle manipulation.…”
Section: Introductionsupporting
confidence: 77%
“…The putamen is known to be crucial for motor activity [24]. The thalamus was identified in pain studies [10]. The postcentral is the SII area as well as the PHIPP, tonsil, and culmen in the cerebellum, which are involved in processing incoming sensory stimulation and high pain sensation of the subjects [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, gabapentin also affected stimulus-induced deactivations, which suggests that the drug has substantial effects on attentional and arousal networks in the brain, in line with its sedative side effects. With respect to clinical pain, we recently confirmed the relationship between the subjective perception of pain intensity and the haemodynamic response, previously only described in healthy volunteers (53)(54)(55)(56)(57)(58). Out of several brain regions in which the magnitude of the FMRI signal encoded the perceived intensity of brush-evoked allodynic pain in neuropathic pain patients, the caudal anterior insula reflected the subjective allodynic pain ratings best (59) (Fig.…”
Section: Application Of Phfmri To Pain Researchsupporting
confidence: 81%
“…However, it is known that pain affects motor output in a variety of ways, ranging from changes in reflex activation to central inhibition to drive the muscle maximally. [35][36][37] We have also shown that experimentally induced knee pain via injection of hypertonic saline into the infrapatellar fat pad in healthy individuals can lead to alterations in vasti control during stair stepping, which are reversed when pain subsides (unpublished data). Thus, pain is a potent driver of changes in neuromotor control.…”
Section: Effect Of Patellar Tapingmentioning
confidence: 84%